1928
DOI: 10.3181/00379727-25-3950
|View full text |Cite
|
Sign up to set email alerts
|

A New Phenomenon of Local Skin Reactivity to B. Typhosus Culture Filtrate.

Abstract: PLATES 6 AI~' V 7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
2

Year Published

1932
1932
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(51 citation statements)
references
References 3 publications
1
48
0
2
Order By: Relevance
“…Local application of small amounts of LPS can sensitize the vascular endothelium and a subsequent LPS challenge can produce vascular lesions with fluid exudation (10). This phenomenon, the local Shwartzman reaction, was initially reported in the rabbit skin (22), but recent reports indicate that the vasculature ofthe kidney is also susceptible to such reactions (23). Studies on the mechanism of pathogenesis of the Shigella group of organisms during the first decade of this century showed that the infusion of filtered broths or heat-killed cultures of Shigella produced, in addition to a neurotoxic syndrome, hemorrhagic enteritis in a variety of experimental animals (24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Local application of small amounts of LPS can sensitize the vascular endothelium and a subsequent LPS challenge can produce vascular lesions with fluid exudation (10). This phenomenon, the local Shwartzman reaction, was initially reported in the rabbit skin (22), but recent reports indicate that the vasculature ofthe kidney is also susceptible to such reactions (23). Studies on the mechanism of pathogenesis of the Shigella group of organisms during the first decade of this century showed that the infusion of filtered broths or heat-killed cultures of Shigella produced, in addition to a neurotoxic syndrome, hemorrhagic enteritis in a variety of experimental animals (24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…However, an alternative model of pregnancy was also postulated, leading to the MedawarShwartzman paradox. The localized Shwartzman reaction of hemorrhagic necrosis is induced in some animals by a priming injection of endotoxin followed by a sublethal intravenous endotoxin injection 24 h later [13]. Identical pathological lesions are observed in pregnant animals after just a single intravenous injection of endotoxin, without requiring a priming injection [14].…”
Section: What Is the Immunology Of Pregnancy?mentioning
confidence: 99%
“…This process is facilitated by the hypotension seen in sepsis. Endotoxins from gram negative bacteria injected 12-14 h apart into rabbits cause the generalized Shwartzman phenomenon [22][23][24], The Shwartzman reaction is regarded as a coagulop athy with massive intravascular coagulation and tissue necrosis, the kidney being the site of predilection. It pro duces microfibrinous thrombosis of afferent arterioles and glomerular capillaries with ensuing renal cortical necrosis.…”
Section: Discussionmentioning
confidence: 99%